(3z-2)(3z+8)=(z-4)(z+4)

Simple and best practice solution for (3z-2)(3z+8)=(z-4)(z+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3z-2)(3z+8)=(z-4)(z+4) equation:


Simplifying
(3z + -2)(3z + 8) = (z + -4)(z + 4)

Reorder the terms:
(-2 + 3z)(3z + 8) = (z + -4)(z + 4)

Reorder the terms:
(-2 + 3z)(8 + 3z) = (z + -4)(z + 4)

Multiply (-2 + 3z) * (8 + 3z)
(-2(8 + 3z) + 3z * (8 + 3z)) = (z + -4)(z + 4)
((8 * -2 + 3z * -2) + 3z * (8 + 3z)) = (z + -4)(z + 4)
((-16 + -6z) + 3z * (8 + 3z)) = (z + -4)(z + 4)
(-16 + -6z + (8 * 3z + 3z * 3z)) = (z + -4)(z + 4)
(-16 + -6z + (24z + 9z2)) = (z + -4)(z + 4)

Combine like terms: -6z + 24z = 18z
(-16 + 18z + 9z2) = (z + -4)(z + 4)

Reorder the terms:
-16 + 18z + 9z2 = (-4 + z)(z + 4)

Reorder the terms:
-16 + 18z + 9z2 = (-4 + z)(4 + z)

Multiply (-4 + z) * (4 + z)
-16 + 18z + 9z2 = (-4(4 + z) + z(4 + z))
-16 + 18z + 9z2 = ((4 * -4 + z * -4) + z(4 + z))
-16 + 18z + 9z2 = ((-16 + -4z) + z(4 + z))
-16 + 18z + 9z2 = (-16 + -4z + (4 * z + z * z))
-16 + 18z + 9z2 = (-16 + -4z + (4z + z2))

Combine like terms: -4z + 4z = 0
-16 + 18z + 9z2 = (-16 + 0 + z2)
-16 + 18z + 9z2 = (-16 + z2)

Add '16' to each side of the equation.
-16 + 18z + 16 + 9z2 = -16 + 16 + z2

Reorder the terms:
-16 + 16 + 18z + 9z2 = -16 + 16 + z2

Combine like terms: -16 + 16 = 0
0 + 18z + 9z2 = -16 + 16 + z2
18z + 9z2 = -16 + 16 + z2

Combine like terms: -16 + 16 = 0
18z + 9z2 = 0 + z2
18z + 9z2 = z2

Solving
18z + 9z2 = z2

Solving for variable 'z'.

Combine like terms: 9z2 + -1z2 = 8z2
18z + 8z2 = z2 + -1z2

Combine like terms: z2 + -1z2 = 0
18z + 8z2 = 0

Factor out the Greatest Common Factor (GCF), '2z'.
2z(9 + 4z) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'z' equal to zero and attempt to solve: Simplifying z = 0 Solving z = 0 Move all terms containing z to the left, all other terms to the right. Simplifying z = 0

Subproblem 2

Set the factor '(9 + 4z)' equal to zero and attempt to solve: Simplifying 9 + 4z = 0 Solving 9 + 4z = 0 Move all terms containing z to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 4z = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 4z = 0 + -9 4z = 0 + -9 Combine like terms: 0 + -9 = -9 4z = -9 Divide each side by '4'. z = -2.25 Simplifying z = -2.25

Solution

z = {0, -2.25}

See similar equations:

| 2y+6+10=18-2y | | -11+r=37 | | (2COSx+1)sinx=0 | | (3z-2)(3z+8)= | | 8+x=13+12x | | 7(a+5)=84 | | 11x^2-31x-54=0 | | 2m+r=28 | | 36x^2=180 | | 2x^2+2x+140=180 | | 14n+2=5n+65 | | -3(w+5-10)=2w+5 | | s+s=900 | | 3x+8x=36 | | 6m-24=30 | | 9x-(3x+8)=7x-12 | | a+(a+2)=10 | | X-5y-20=0 | | 40+16x+4=23x+2 | | (13x+45)+(12x-40)=180 | | 175+(17x-3)=17x+8 | | 75+30h=75+45h | | y=15-12.7272727273/4 | | .3*x=63 | | 8x-25=6x+9 | | pr=2i+2a | | 24x^3+8x^2-10x=0 | | 2x^4-6x^3+7x^2-21x=0 | | (5y+5)=(7y-a) | | 15-x/4=50-3x | | 4x+8x-7+x=162 | | 3x+120+y=2x+y |

Equations solver categories